Structural analysis of normal and mutant insulin receptors in fibroblasts cultured from families with leprechaunism. - Endo, F (1987)
Leprechaunism is an inherited disorder characterized by insulin resistance and intrauterine growth restriction. In this study we analyze insulin binding and subunit structure of the insulin receptor in dermal fibroblasts cultured from three unrelated families whose probands (Ark-1, Atl, and Minn) were affected by leprechaunism. Cells cultured from all three probands had markedly reduced insulin binding at equilibrium. Fibroblasts cultured from the parents of Ark-1 and Atl had partial and differing degrees of impairment in insulin binding. The structure of the alpha subunit of insulin receptors was analyzed by cross-linking 125I-insulin to plasma membranes. A major band of 350 kilodaltons (kD) (corresponding to the heterotetrameric insulin receptor alpha 2 beta 2) was observed in control and leprechaun fibroblasts. The relative amount of radioactivity cross-linked to plasma membranes reflected the genetic variations seen in insulin binding to intact cells. In reducing gels, 125I-insulin was cross-linked equally to a 250-kD (alpha-alpha dimer) and a 125-kD (alpha monomer) protein in cells from controls, the parents of Ark-1 and Atl, and probands Atl and Minn. By contrast, cells from the Ark-1 proband had diminished cross-linking of alpha-alpha dimers. The ratio of dimer to monomer in cells from controls was 0.93 +/- 0.06, and that in cells from Ark-1 was 0.31 +/- 0.19 (P less than .01). Beta-subunit structure and function was analyzed by studying insulin-enhanced autophosphorylation. Although maximal stimulation of beta-subunit phosphorylation was reduced to 30% in proband Ark-1 fibroblasts, this reduction was quantitatively related to reduced insulin binding. These results indicate that mutations causing severe insulin resistance and defective insulin binding are transmitted with autosomal recessive patterns of inheritance and that heterogeneity exists for these mutations. The mutation in pedigree Ark-1 most likely produces conformational changes in alpha-subunit interaction.